ASSESSING CHANGES IN THE EXAMINATION CONTENT OF A MATHEMATICS COURSE ON PRE-COMMERCE STUDENTS' PERFORMANCE IN PUBLIC UNIVERSITY - Farah Hayati Mustapa; Che Maznah Mat Isa, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Previous studies suggest that alterations in examination content may lead to a shift in students’ performance and learning outcomes. Despite the importance of these issues, there is a lack of comprehensive research examining how specific changes in exam content affect mathematics student outcomes across different educational settings. Thus, this comparative study examines the impacts of changes in examination content of intensive mathematics course affecting pre-commerce students’ performance by comparing the grade distributions and the final exams marks obtained by the students across two semesters. The findings suggest that modifications in the final exam content, such as the exclusion of index and logarithm topics from the final exams alone, do not seem to have a significant impact on the students’ marks and grades. The weightage of assessments seems to influence students’ final achievement too. This shift occurred alongside significant changes in examination content, including the introduction of new topics, the omission of some topics and a redistribution of marks across subjects in both formative and summative assessments. The analysis highlights the importance of careful curriculum planning and the need for targeted student support when changes to assessment structures are implemented.